Implementasi MVVM Dan Framework Jetpack Compose Pada Aplikasi Hukum Berbasis Android - Aziz Musthafa; Dihin Muriyatmoko; Abdullah Hikmatyar Priandika (Prosiding SISFOTEK, 2024)
This research discusses the development of Android-based legal applications using Model-View-ViewModel (MVVM) architecture and Jetpack Compose framework. The purpose of this research is to improve the access and understanding of the Indonesian people to legal aid through an efficient and user-friendly mobile application. The research method used is Software Development Life Cycle (SDLC) with a waterfall model that includes the stages of needs analysis, design, implementation, testing, and maintenance. Data was collected through a questionnaire distributed to 107 respondents aged 17-40 years to measure their understanding of the law and access to legal aid. The results of the analysis showed that 67% of the respondents knew how to get legal aid, but did not know the details of how. The developed app has several key features, such as a list of laws and regulations, AI Q&A, and lawyer consultation. The implementation of Jetpack Compose on the login, register, home, chatbot, regulations, and regulation details pages shows efficiency and ease in developing an interactive and responsive user interface. Application testing is carried out through verification by media experts, application users, and black box tests. The test results show that the application functions properly and meets user needs. The conclusion of this research is that the use of MVVM architecture and Jetpack Compose can speed up the development process and facilitate the maintenance of Android-based legal applications. This application is expected to provide practical and effective solutions in obtaining legal assistance and increasing legal understanding among the people of Indonesia.